Access to Medicines and Pharmaceutical Patents:Corporate Responsibility to Respect in the Pharmaceutical Industry - Gözükara,Dilan Gökce (2014)
The U.N. Guiding Principles on Business and Human Rights is the final work of the meticulous mandate upheld by the Special Representative of the Secretary-General between 2005 and 2011. It consists of three pillars, namely, the state duty to protect against human rights abuses by third parties, including business, the corporate responsibility to respect human rights, and access by victims to effective remedy. The focus of this thesis is on the second pillar, specifically the corporate responsibility of patent-holding pharmaceutical companies to respect the right to health in access to medicines context. The research question that this thesis seeks to answer is what meaning the corporate responsibility to respect human rights as framed by the U.N. Guiding Principles signifies for patent-holding pharmaceutical companies in the access to medicines context, more specifically, whether it is comprehensive enough to meet the right to health requirements or not. The thesis initially establishes that the term ‘respect’ is meant to correlate with its meaning in human right law, which refers to non-infringement or ‘doing no harm’. Subsequently, the thesis avails itself of the right to health framework as a reference point to indicate the adverse human rights impacts of patent-holding pharmaceutical companies. As a response to these adverse impacts, specific corporate actions that should be taken are suggested, which often require initiative from companies such as price reductions in life-saving medicines through participation in multi-stakeholder initiatives or engaging in voluntary licensing agreements. Justifications to support the aforementioned actions are also provided to make clear that the scope of corporate responsibility to respect in fact allows for broader interpretation of 'respect' in certain circumstances.